ANALISIS KONTEN PADA PERSEPSI ATLET WANITA MUSLIM TERHADAP ATURAN BERPAKAIAN PADA EVENT BOLA VOLI PASIR DI INDONESIA - Prayanti, Yulia; Sulhaini, Sulhaini; Saufi, Akhmad (Jurnal Magister Manajemen, 2020)
This study aims to determine how to conduct an analysis in a phenomenon to find out the perception of Moslem female athletes of the dress code at beach volleyball events in Indonesia with a content analysis approach. Data collection was carried out through observation, interviews and documentation on Moslem female athletes in Indonesia. The results of this study found three main categories from 14 themes which are interrelated dimensions, they are authenticity and professionalism orientation, moderate orientation and athlete’s achievement. These findings indicate that the relationship between perceptions, attitudes and the use of dress codes for Moslem female athletes in beach volleyball events.